2006
DOI: 10.1158/1078-0432.ccr-06-0883
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Sequential Low-Dose 5-Aza-2′-Deoxycytidine Plus High-Dose Intravenous Bolus Interleukin-2 in Patients with Melanoma or Renal Cell Carcinoma

Abstract: Purpose: The silencing of gene expression through DNA methylation contributes to defects in antigen presentation and apoptosis in melanoma and renal cell cancer. To determine how a hypomethylating agent would modulate the toxicity and antitumor activity of immunotherapy, we initiated a phase I trial of 5-aza-2 ¶-deoxycytidine (decitabine) plus high-dose interleukin 2 (IL-2). Experimental Design: Patients received s.c. decitabine daily  5 days on weeks 1 and 2 of a 12-week cycle. High-dose IL-2, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 21 publications
2
91
1
1
Order By: Relevance
“…Recently, a phase I trial of low-dose 5-Aza-dC plus interleukin-2 was performed in patients with malignant melanoma (50). Among 16 patients, the response rate was 31% (50). Although global methylation was evaluated using repetitive sequences in this study, the methylation status of specific genes affected by 5-Aza-dC treatment were not examined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a phase I trial of low-dose 5-Aza-dC plus interleukin-2 was performed in patients with malignant melanoma (50). Among 16 patients, the response rate was 31% (50). Although global methylation was evaluated using repetitive sequences in this study, the methylation status of specific genes affected by 5-Aza-dC treatment were not examined.…”
Section: Discussionmentioning
confidence: 97%
“…We expect that transcriptional silencing of the SOCS3 gene by aberrant methylation might contribute to resistance of malignant melanoma cells to IFN treatment. Recently, a phase I trial of low-dose 5-Aza-dC plus interleukin-2 was performed in patients with malignant melanoma (50). Among 16 patients, the response rate was 31% (50).…”
Section: Discussionmentioning
confidence: 99%
“…A daganatokban ezen enzimek gátlásával (DNMT-inhibitor például a decitabin, HDAC-inhibitor például a valproát) visszafordítható a tumorszuppresszor gének aberráns hipermetilációja, ami géncsendesítést okozott, ezáltal expressziójuk növekedésével újra el tudják látni a sejtosztódást fékező funkciójukat. A jövőben melanomás betegek is profi tál-hatnak ezen kutatások eredményeiből [34,35]. Emellett a cutan melanomák 60%-ában patológiásan működő PI3K/AKT/mTOR szignáltranszdukciós útvonal nemcsak a tumorszuppresszor PTEN által gátolható, hanem célzottan, AKT-inhibitorokkal (például perifosin) és mTOR-gátlókkal (például temsirolimus, everolimus) is.…”
Section: áBraunclassified
“…However, injection of decitabine in nude mice carrying melanoma xenografts led to resensitization to interferon treatment (Reu et al, 2006). A phase I clinical trial of decitabine together with interleukin-2 in melanoma patients further showed an objective response in 31% of the patients (Gollob et al, 2006). Likewise, preclinical data also suggests that epigenetic therapy can induce radiosensitization and enhance current conventional treatment regimens (Munshi et al, 2005).…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%